Production and consumption of gentrification aesthetics in Shanghai's M50. Issue 1 (1st September 2021) - Ning, Yajing; Chang, T.C.
Abstract: The transformation of artist communities into cultural consumption sites is a notable trend in many post‐reform Chinese cities. Once enclaves for creative freelancers, artist communities have seen an influx of tourists, cultural commodification, and socio‐spatial changes. While much has been written about the role of state and art practitioners in effecting gentrification, less attention has been given to the transformation of gentrified sites into consumable spaces and how they are received. Drawing on the case of 50 Moganshan Road (M50), a former industrial zone and artist colony in Shanghai that has become a cultural district, this paper sheds light on the relationships between urban regeneration, artistic production, and aesthetic consumption. The study applies the idea of gentrification aesthetics, a concept that bridges middle‐class consumption with inner‐city regeneration. By extending the concept to an art space shaped by production and consumption forces, a more holistic understanding of urban redevelopment is afforded, along with its attendant social, cultural, and personal dimensions and challenges. Abstract : Drawing on the case of 50 Moganshan Road (M50), a former industrial zone and artist colony in Shanghai that has become a cultural district, this paper sheds light on the relationships between urban regeneration, artistic production and aesthetic consumption. The study applies the idea of gentrification aesthetics, a concept that bridges middle‐class consumption with inner‐city regeneration. By extending the concept to an art space shaped by production and consumption forces, a more holistic understanding of urban redevelopment is afforded, along with its attendant social, cultural, and personal dimensions and challenges.